The genome of kenaf (Hibiscus cannabinus L.) provides insights into bast fibre and leaf shape biogenesis. Issue 8 (30th January 2020) - Zhang, Liwu; Xu, Yi; Zhang, Xingtan; Ma, Xiaokai; Zhang, Lilan; Liao, Zhenyang; Zhang, Qing; Wan, Xuebei; Cheng, Yan; Zhang, Jisen; Li, Dongxu; Zhang, Liemei; et al.
Summary: Kenaf is an annual crop that is widely cultivated as a source of bast (phloem) fibres, the phytoremediation of heavy metal‐contaminated farmlands and textile‐relevant compounds. Leaf shape played a unique role in kenaf improvement, due to the inheritance as a single locus and the association with fibre development in typical lobed‐leaf varieties. Here we report a high‐quality genome assembly and annotation for var. 'Fuhong 952' with 1078 Mbp genome and 66 004 protein‐coding genes integrating single‐molecule real‐time sequencing, a high‐density genetic map and high‐throughput chromosome conformation capture techniques. Gene mapping assists the identification of a homeobox transcription factor LATE MERISTEM IDENTITY 1 ( HcLMI1 ) gene controlling lobed‐leaf. Virus‐induced gene silencing (VIGS) of HcLMI1 in a lobed‐leaf variety was critical to induce round (entire)‐like leaf formation. Candidate genes involved in cell wall formation were found in quantitative trait loci (QTL) for fibre yield and quality‐related traits. Comparative genomic and transcriptome analyses revealed key genes involved in bast fibre formation, among which there are twice as many cellulose synthase A (CesA) genes due to a recent whole‐genome duplication after divergence from Gossypium . Population genomic analysis showed two recent population bottlenecks in kenaf, suggesting domestication and improvement process have led to an increase in fibre biogenesis and yield. This chromosome‐scale genome provides an important framework and toolkit for sequence‐directed genetic improvement of fibre crops.